2010
DOI: 10.1021/jp9101288
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electronic Properties of the Hydrogenated ZrCr2 Laves Phases

Abstract: A series of hydrogenated cubic C15 and hexagonal C14 ZrCr 2 Laves phases were studied by means of semiempirical extended Hu ¨ckel tight-binding, ab initio density functional theory methods and maximally localized Wannier functions, with a goal to find the most energetically favorable positions of interstitial H atoms in the host unit cells. We consider situations with one or two H atoms per primitive cell. Crystalorbital overlap population studies, performed for the C15 structure, show repulsion between two hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
7
16
0
Order By: Relevance
“…(a) (b) [13] Hydrogen occupation occurs first at the A2B2 site, next at the AB3 site, and finally at the B4 site [14][15][16][17]. Furthermore, the ratio between the tetrahedral sites is 12 A2B2, 4 AB3, and 1 B4 for both C14 and C15 structures.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…(a) (b) [13] Hydrogen occupation occurs first at the A2B2 site, next at the AB3 site, and finally at the B4 site [14][15][16][17]. Furthermore, the ratio between the tetrahedral sites is 12 A2B2, 4 AB3, and 1 B4 for both C14 and C15 structures.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, the model for e/a at the C14/C15 threshold (C14:C15 = 1:1) was further improved to include the contribution from the A-site atoms by incorporating the average chemical potential of the A-site atoms [24]. [13] Hydrogen occupation occurs first at the A 2 B 2 site, next at the AB 3 site, and finally at the B 4 site [14][15][16][17]. Furthermore, the ratio between the tetrahedral sites is 12 A 2 B 2 , 4 AB 3 , and 1 B 4 for both C14 and C15 structures.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of interstitial metal hydrides, the molecular hydrogen in the gas is split into atomic hydrogen on the surface of the material and then, it diffuses into the atomic structure of the host metal. In these hydrides, hydrogen acts as a metal and forms a metallic bond [29]. A large number of different metallic compounds exist that will absorb hydrogen in this manner.…”
Section: Solid Storage Of Hydrogen (Ssh 2 )mentioning
confidence: 99%
“…According to Somenkov et al [16], occupation of g-and e-sites in Laves phase compounds is lattice size-dependent. For ZrCr 2 system, g-sites, with largest interstices, are preferentially occupied [15]. Eberle reported that for ZrCr 2 H x alloys with x < 2.5, only gsites are occupied [17].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen in ZrCr 2 occupies tetrahedral interstitial sites. Three types of interstitial sites may be identified: those coordinated by 2Cr and 2Zr atoms (g-sites), 3Cr and 1Zr atoms (e-sites) and 4Cr atoms [15]. According to Somenkov et al [16], occupation of g-and e-sites in Laves phase compounds is lattice size-dependent.…”
Section: Introductionmentioning
confidence: 99%